Production of oxalic acid by electrochemical reduction of CO2 using silver-carbon material from babassu coconut mesocarp. (December 2020) - Costa, Rubens S.; Aranha, Bruna S.R.; Ghosh, Anupama; Lobo, Anderson O.; da Silva, Everson T.S.G.; Alves, Diego C.B.; Viana, Bartolomeu C.
Abstract: The present study provides an efficient carbon dioxide (CO2 ) reduction process to produce oxalic acid with approximately 29% faradaic efficiency (based on HPLC) using a carbon material from babassu biomass coupled with silver. A new carbon-silver hybrid material has been prepared from babassu mesocarp by hydrothermal carbonization; this material initiates the electrochemical reduction of CO2 at a lower potential and catalyzes the conversion of CO2 into oxalic acid. To evaluate the catalytic potential of this reaction, other materials, such as glassy carbon and hydrothermal carbon, which generated a higher cathodic current density, were tested at the same potential. The rate of CO2 reduction was found to be increased at low potentials in the presence of the hybrid carbon-silver material synthesized by a one-pot hydrothermal method from babassu biomass in 48 h (Ag@C-48). Graphical abstract: Image 1 Highlights: Hybrid hydrothermal carbon/silver catalyst for CO2 reduction from babassu coconut mesocarp as the carbon source is reported. Synthesis parameter, generating carbon spheres of different sizes that influence the efficiency of the obtained catalyst. High yield oxalic acid production by CO2 reduction with 28.95% faradaic efficiency has been achieved.